Changes in bone mineral density in patients with recent onset, active rheumatoid arthritis. Issue 6 (20th July 2007) - Güler-Yüksel, M; Bijsterbosch, J; Goekoop-Ruiterman, Y P M; de Vries-Bouwstra, J K; Hulsmans, H M J; de Beus, W M; Han, K H; Breedveld, F C; Dijkmans, B A C; Allaart, C F; Lems, W F
Abstract : Objectives: We examined the effects of four different treatment strategies on bone mineral density (BMD) in patients with recently diagnosed, active rheumatoid arthritis (RA) and the influence of disease-related and demographic factors on BMD loss after 1 year of follow-up in the BeSt trial. Methods: BMD measurements of the lumbar spine and total hip were performed in 342 patients with recent onset RA at baseline and after 1 year. Multivariable regression analyses were performed to determine independent associations between disease and demographic parameters and BMD loss after 1 year. Results: Median BMD loss after 1 year was 0.8% and 1.0% of baseline in the spine and the hip, respectively. No significant differences between the treatment groups, including corticosteroids and the anti-tumour necrosis factor-α infliximab, were observed with regard to BMD loss after 1 year of treatment. Joint damage at baseline and joint damage progression according to the Sharp–van der Heijde score were independently associated with more BMD loss after 1 year. The use of bisphosphonates independently protected against BMD loss. Conclusions: After 1 year of follow-up in the BeSt study, we did not find differences in BMD loss between the four treatment strategies, including high doses of corticosteroids and anti-tumour necrosis factor-α. Joint damage and joint damage progression are associated with high BMD loss, which emphasises that BMD loss and erosive RA have common pathways in their pathogenesis.